Territorial division and income affluence – analysis using two-level logit models - Sączewska-Piotrowska, Anna (Podział terytorialny a zamożność dochodowa – analiza z wykorzystaniem dwupoziomowych modeli logitowych, 2018)
The aim of the paper was to assess differentiation of the occurrence of households’ income affluence in Poland between subregions. An analysis was conducted using two-level logit models without explanatory variables (null model) and with explanatory variables at household level (random intercept model and random slope model). The variables were related to the characteristics of the household and its head. The conducted analysis allowed to state that the occurrence of affluence is differentiated between subregions in the null model as well as in the model with explanatory variables
Econometrics = Ekonometria, 2018, Vol. 22, No. 4, s. 65-78
Keywords: two-level logit model; multilevel modelling; affluence; income; household